(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Metrology in the broadest sense is the science of measurements, methods and means, ensuring their unity, and ways to achieve the required accuracy. Metrology serves as the theoretical basis for measuring technology. metrology deals with the theory and practice of ensuring the uniformity of measurements. And the more measuring technology develops, the more important metrology becomes, creating and improving the theoretical foundations of measurements, summarizing practical experience in the field of measurements and guiding the development of measuring technology.